UPAYA DIPLOMASI BUDAYA KOREA SELATAN MELALUI KOREA TOURISM ORGANIZATION (KTO) JAKARTA PERIODE 2017-2022 - Azka Khaleeda Wibawa, (2023)
This research is discussing about South Korea's cultural diplomacy effort through Korea Tourism Organization (KTO) Jakarta 2017-2022 period. The year chosen was made for the reason of showing the differences between the strategies made by KTO Jakarta before the pandemic, during the pandemic, and after the pandemic (entering the new normal era). This research uses the concept of soft power, public diplomacy and cultural diplomacy. This research uses a descriptive qualitative method with two data resources, which is primary and secondary through documents, related data, previous research, and interview with KTO Jakarta. Cultural diplomacy itself is an effort made to achieve its national interests by emphasizing and promoting its culture, such as education, sports, and tourism. This research written by analysing cultural diplomacy forms by Tulus Warsito, which is exhibition and exchange mission. KTO Jakarta's strategies to do the cultural diplomacy through some works, such as carrying out offline, online, and hybrid events, having collaborations with artists, influencers, and TV station. Through this research, author found that cultural diplomacy that KTO Jakarta did is success, following by the number of tourists from Indonesia to South Korea. Besides that, author also found that the number of tourists from South Korea to Indonesia is high, this also comes from the cultural diplomacy.